Development and validation of the Health Activation Scale for Children (HAS-C): an important intermediate outcome measure for health promotion initiatives - Lixia Ge; Joseph Molina; Ramakrishnan Karthigayan; Hui Ting Foo; Marcus Tang; Rochelle Chua; Chin Fung Ong (BMC, 2024)
Abstract Background Valid and reliable measures for assessing health activation in school-aged children are currently lacking. This study aimed to develop a scale to measure health activation and evaluate its psychometric properties among English-speaking primary school children in Singapore. Methods The development of the Health Activation Scale for Children (HAS-C) involved an extensive literature review, expert consultations, cognitive interviews with primary school children, and thorough discussions for dimension and item refinement. A cross-sectional study was conducted with 597 children aged 8 to 12 years, recruited from four mainstream primary schools, comprising 50.1% boys and 64.8% Chinese students. The potential scale, along with other measures, was independently completed by the children. Descriptive statistics were provided for individual scale items. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed to assess factorial validity. Convergent validity was examined by correlating the scale scores with scores of health confidence and self-efficacy measures. Hypothesis-testing validity was evaluated by assessing the scale's correlation with self-reported health behaviours, including daily consumption of vegetables and fruits, time spent on sedentary activities and physical activities. Internal consistency reliability was measured using Cronbach's alpha. Results EFA suggested a three-factor structure for the 12-item HAS-C, which was subsequently confirmed by CFA with a good model fit. All three HAS-C dimension scores demonstrated moderate correlations (rho = 0.34-0.52) with health confidence and self-efficacy measures, indicating good convergent validity. They were positively correlated with more vegetable and fruit intakes, more time spent on exercises, and negatively correlated with time spent on sedentary activities, supporting hypothesis-testing validity. Internal consistency reliability for individual HAS-C dimensions was generally acceptable, with Cronbach's alpha values of 0.70 or above. Conclusion The 12-item multi-dimensional HAS-C exhibited good validity and reliability, making it a valuable tool for assessing health activation in primary school-aged children.